High Harmonic Reduction Using Passive Filters of Mountain Steel Company - Asmahan Y. Husen; Kamal H.Younis; Ameen A. Fatah (Zanco Journal of Pure and Applied Sciences, 2021)
An increasing amount of power electronics has created an immediate effect on the value of the electrical power source. Both of high control manufacturing loads and national loads explain harmonic in the system voltage. In this paper, characterized by nonlinear loads, are classified into two types of harmonics, current source harmonics, and voltage source harmonics. Harmonic distortion has usually been deleted via the usage of LC passive filter. The proposed technique is to get lower THD as long as possible and high power factor and high efficiency, properties of the passive filter is demonstrated in experiments for harmonic compensation in MOUNTAIN STEEL Company before and after filtering, by taking the voltage THD of a different time in a day.